Adolescents Strength Profile of Hope Based on Demographic Factors - Dody Hartanto; Sunaryo Kartadinata; Ahman Ahman; Ilfiandra Ilfiandra (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This research aims to reveal ‘hope' of Indonesian adolescents especially in Bantul regency of Special Region of Yogyakarta. Data were gathered from 106 adolescents consisting of 38 males and 68 females (16 -18 years old) from high schools.The instruments of this study was a hope scale in the form of semantic deferential scale ranged from 1 to 8 (1= very inappropriate, 8 = very appropriate). The data analysis of this study was descriptive statistics. The result of the study showed that the hope of female students is higher than male students. In agency thinking, male students are higher than female students, otherwise, in pathways thinking, female students are higher than male students. Based on the parents' occupation, those who work in private sector have high hope. Conversely, the students whose parents are farmers have a low hope. The lowest scale of pathways thinking was obtained by the students whose parents are farmers as well as in the agency showed that the students whose parents are labours obtained the lowest scale